Estudo da demanda energética e desagregação do solo em diferentes sequências operacionais de preparo periódico - Salvador, Nilson (2010)
The correct selection of the operational sequence of soil tillage is essential to reduce the cost of agricultural mechanization in the regions that mobilize intensively the soil. The objective of this work was to evaluate the energetic demand and disaggregation of the soil in different operational sequences of subsoiling and systems of periodic soil tillage. The experimental design was blocks at random, in a factorial model 5 x 2 with 5 replications, being 5 tillage systems (D - Disc plow, Dn - disc plow followed at leveler rail, G - weight rail, Gn - weight rail followed of leveler rail and E - Stirrer. ) and two sequencies of subsoiling (SP - Subsoiling - tillage and PS - Tillage - subsoiling). There were evaluated the energetic demand, fuel consumption by area and the soil disaggregation. The results showed that the operational sequence tillage of the soil - subsoiling (PS) had a lower energetic requirement, except for the stirrer, the sequence tillage the soil - subsoiling consumed less fuel and soil disaggregation didn't show statistic variation.